Determination of the early initiation of breast feeding in low-middle income country: a systematic review - Rahmawati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
WHO recommends Early Initiation of Breastfeeding (EIBF), which means direct breastfeeding to newborns within the first hour of life. However, nowadays, EIBF is not often carried out by mothers, which increases the risk of infant death. This review investigates studies that identify factors associated with EIBF practices. We conducted a systematic review to answer the aforementioned aims. Factors associated, mother-child, and early initiation breastfeeding were used as initial keywords, which were further developed using Medical Subject Headings. Four databases, including Sciencedirect, pubmed, Cochrane, and wiley online library were searched for potential articles. We also searched the references in addition to the main search. We included 12 articles in this review. Type of delivery assisted and mode of delivery were the most influence factors associated to EIBF. Other factors that are frequently showed up in analysis of studies included such as ANC/PNC visits, households wealth, place of residence, and birth order. Addressing the EIBF problem requires multi-sectoral and complex repair efforts. The results of this review show promising problem mapping to initiate a transformation. The type of delivery assisted and the mode of delivery were the most influential factors, in addition to other factors such as ANC/PNC visits, household wealth, place of residence, and birth order. Therefore, health workers must be aware of and communicate with clients regarding the urgent need for early breastfeeding.